2015
DOI: 10.1007/s00270-015-1182-4
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally Inserted Central Catheter-Related Infections in a Cohort of Hospitalized Adult Patients

Abstract: Chemotherapy, auto/allograft, and anti-coagulant therapy are important predictors of PICC-associated infections. A careful assessment of these risk factors may be important for future success in preventing PICC-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
(40 reference statements)
3
30
2
1
Order By: Relevance
“…In contrast, Chopra and colleagues 15 carried out a systematic review and meta-analysis of the risk of bloodstream infections associated with PICCs as compared to central venous catheters and reported a rate of 5.2% (76/1473) for inpatients and 0.45% (117/25 822) for outpatients. In a study of similar design to ours, Bouzad and colleagues 16 reported an incidence of catheter-related bloodstream infections of 27 episodes, or 1.43/1000 catheter days, in a sample of 923 PICC placements; in the subcohort of patients with hematological disease, the overall rate of infectious complications was 3.13/1000 catheter days.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, Chopra and colleagues 15 carried out a systematic review and meta-analysis of the risk of bloodstream infections associated with PICCs as compared to central venous catheters and reported a rate of 5.2% (76/1473) for inpatients and 0.45% (117/25 822) for outpatients. In a study of similar design to ours, Bouzad and colleagues 16 reported an incidence of catheter-related bloodstream infections of 27 episodes, or 1.43/1000 catheter days, in a sample of 923 PICC placements; in the subcohort of patients with hematological disease, the overall rate of infectious complications was 3.13/1000 catheter days.…”
Section: Discussionsupporting
confidence: 62%
“…(7%), E. coli (5%) and Acinetobacter spp. (4%); these prevalence rates are in accordance with the results reported in a study conducted from 2011 to 2013 4 . Our study also supported the retrospective survey conducted in Italy except for CONS which was reported at 34% and the result of our study showed 16%; that retrospective study was conducted on oncological patients which were more prone to CONS infections…”
Section: Mrsa: Methicillin Resistant Staphylococcus Aureussupporting
confidence: 81%
“…The rates of removal due to complications were 3.5% to 48% with PICCs [4][5][6]12,14,15,20,[23][24][25][26][27]29,32,33,35,37,38,45,46 compared to 67% to 81.2% with PIVCs 6,14 and 26% to 78% with CICCs. 5,6,33 In the study by Cotogni et al 5 in which catheters were used for home parenteral nutrition in patients with cancer, the ratio of complications leading to removal over total complications was significantly lower for PICCs versus CICCs (55% vs. 85%, P < 0.05).…”
Section: Safety Outcomesmentioning
confidence: 94%
“…Accidental catheter removal was reported in 1% to 8.9% of patients with PICCs across studies 4,23,26,29,31,35,44 versus 7.8% of patients with PIVCs reported in a single study that met the inclusion criteria. 14 Catheter blockage occurred in 0% to 38% of patients with PICCs 4,5,12,14,15,17,19,23,26,28,29,[32][33][34][35]46,47 compared to 0% to 16% of patients with CICCs. 5,17,28,33 The proportion of patients reporting catheter migration/dislocation was 0% to 7.7% with PICCs 5,14,30,33,37 compared to 9.6% to 15% with CICCs.…”
Section: Safety Outcomesmentioning
confidence: 99%
See 1 more Smart Citation